Perbaikan Tanah (Soil Improvement) Dengan Penambahan Campuran Karang Kapur Dan Pasir Sungai Di Kampung Burmeso, Kab. Mamberamo Raya Terhadap Nilai Cbr Untuk Meningkatkan Daya Dukung Tanah Dasar - Kanggunum, Derek Aleks (Syntax Literate, 2025)
In this study, to determine the amount of carrying capacity value of the carrying capacity of the base soil was carried out using the California Bearing Ratio (CBR) method of soaking laboratory (soaked) and soil density test (proctor), testing was carried out in the laboratory of the National Road Implementation Center, black soil in Abepura. There are several tests carried out, including Basic Properties, including water content tests, liquid limits, plastic limits and specific gravity, Engineering properties, including proctor standard compaction experiments and laboratory CBR (soaked). From the results of research that has been tested at the BPJN Jayapura laboratory in Tanah Hitam, Abepura. Related Analysis of the physical characteristics of local soils, river sand and limestone corals from the Burmeso Quarry. The effect of adding limestone corals and river sand can increase the carrying capacity of the subsoil where the results of the CBR test of the laboratory of the base soil are 4.8% and the results of the research with a mixed combination of the immersion CBR test can be obtained a CBR value of 42.0%. From these results, it shows that the addition of limestone corals and river sand, which has an increase of 11.42% of the results, shows that the addition of limestone corals and river sand is able to increase the carrying capacity of the groundsoil.